Defining "county": A mixed‐methods inquiry of county emergency medicine residency programs. (29th September 2021) - Buchanan, Jennie A.; Moreira, Maria; Taira, Taku; Byyny, Richard; Jarou, Zachary; Taylor, Todd Andrew; Sungar, W. Gannon; Angerhofer, Christy; Dyer, Sean; White, Melissa; Amin, Dhara; D. Lall, Michelle; et al.
Abstract: Introduction: There is no clear unified definition of "county programs" in emergency medicine (EM). Key residency directories are varied in designation, despite it being one of the most important match factors for applicants. The Council of Residency Directors EM County Program Community of Practice consists of residency program leadership from a unified collective of programs that identify as "county." This paper's framework was spurred from numerous group discussions to better understand unifying themes that define county programs. Methodology: This institutional review board–exempt work provides qualitative descriptive results via a mixed‐methods inquiry utilizing survey data and quantitative data from programs that self‐designate as county. Unique treatment, analysis and critique: Most respondents work, identify, and trained at a county program. The majority defined county programs by commitment to care for the underserved, funding from the city or state, low‐resourced, and urban setting. Major qualitative themes included mission, clinical environment, research, training, and applicant recommendations. Comparing the attributes of programs by self‐described type of training environment, county programs are typically larger, older, in central metro areas, and more likely to be 4 years in duration and have higher patient volumes when compared to community or university programs. When comparing hospital‐level attributes of primary training sites county programs are more likely to be owned and operated by local governments or governmental hospital districts and authorities and see more disproportionate‐share hospital patients. Implications for education and training in EM: To be considered a county program we recommend some or most of the following attributes be present: a shared mission to medically underserved and vulnerable patients, an urban location with city or county funding, an ED with high patient volumes, supportive of resident autonomy, and research expertise focusing on underserved populations.